2020
DOI: 10.1016/j.brs.2020.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Rotational field TMS: Comparison with conventional TMS based on motor evoked potentials and thresholds in the hand and leg motor cortices

Abstract: Background: Transcranial magnetic stimulation (TMS) is a rapidly expanding technology utilized in research and neuropsychiatric treatments. Yet, conventional TMS configurations affect primarily neurons that are aligned parallel to the induced electric field by a fixed coil, making the activation orientationspecific. A novel method termed rotational field TMS (rfTMS), where two orthogonal coils are operated with a 90 phase shift, produces rotation of the electric field vector over almost a complete cycle, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…The rotation of the E-field could be contributing to TIS stimulation. For example, rotational field TMS, applied using two perpendicular figure-of-eight TMS coils driven with the same current waveforms with a 90° phase shift, demonstrated lower thresholds and stronger evoked responses (Rotem et al, 2014;Roth et al, 2019Roth et al, , 2020. The rotational E-field is hypothesized to sweep across the neural population and simultaneously activate neurons with different directional sensitivity.…”
Section: Non-aligned E-fieldsmentioning
confidence: 99%
“…The rotation of the E-field could be contributing to TIS stimulation. For example, rotational field TMS, applied using two perpendicular figure-of-eight TMS coils driven with the same current waveforms with a 90° phase shift, demonstrated lower thresholds and stronger evoked responses (Rotem et al, 2014;Roth et al, 2019Roth et al, , 2020. The rotational E-field is hypothesized to sweep across the neural population and simultaneously activate neurons with different directional sensitivity.…”
Section: Non-aligned E-fieldsmentioning
confidence: 99%
“…We have also developed an mTMS system with a large general-purpose 5-coil transducer [14]. Previous studies have also combined two figure-of-eight coils to produce a rotating E-field in a single TMS pulse capable of reducing the orientation sensitivity of neuronal excitation [17,18]. In this study, we developed a compact 2-coil transducer tailored for controlling the orientation of the peak induced E-field to allow high-resolution mappings of the neuronal sensitivity to the TMS pulse orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was concluded that excitatory and inhibitory neuronal mechanisms exhibit a critical sensitivity to the stimulus orientation. The observations of Souza et al [20] and Ziemann et al [8] were based on the CS and TS intensities set relative to the resting motor threshold (RMT) only in the AM orientation and not in the PM orientation, in which the RMT can be about 30% higher than in the AM orientation [24]. Therefore, it remains unclear whether the neuronal mechanisms engaged in the inhibitory and facilitatory phenomena are truly affected by the stimulus orientation rather than a decrease in the relative stimulation intensity.…”
Section: Introductionmentioning
confidence: 99%